Rapid Measurements of Damaged Areas and Cavities Formed on Highways Caused by Heavy Rain Falls, Earthquakes or Similar Catastrophes - Bhattacharya Syama P.; Ghosh Asis (Selected Scientific Papers: Journal of Civil Engineering)
An abnormal damaged area and the volume of a deep cavity formed underneath this area on a highway cannot be measured correctly by any of the existing methods. However, in this study Bhattacharya’s theorem was applied for the measurement of an abnormal area with success. An abnormal volume of the cavity formed underneath of this damaged area was also measured by a newly proposed rule of volume measurement. The authors hope that the theorem and the rule described in this paper can be applied in the measurements of various abnormal damaged areas and cavities of highways for quick restoration of the spots. In fact the method of area measurements as well as the measurements of volumes of the cavities formed underneath the area can be done in the small or large scale if needed. Measurements of volumes by filling method of the cavities by foam beads however can be removed from the cavities quickly by an electric vacuum suction machine and the beads are reusable many times.